A novel homozygous splice donor variant in the LRPPRC gene causing Leigh syndrome with epilepsy, a French-Canadian disorder in a Saudi family: case report - Muthaffar, Osama Y.; Abdulkareem, Angham Abdulrhman; Ashi, Abrar; Naseer, Muhammad Imran (Frontiers in Pediatrics, 2023)
Background: Mitochondria is a cellular power house. Tissues are involved in frequent energy consumption and any failure or irregularity in the continuous energy production could lead to abnormalities. The LRPPRC is one of mitochondrial related functions genes; variations in these genes are responsible for complex phenotypes affecting brain, liver and muscles. Materials and methods: In this study, a family with Leigh syndrome like phenotype was enrolled. Whole exome sequencing (WES) followed by Sanger sequencing was performed for molecular diagnosis. Results: WES data analysis short-listed a novel splice-site variant (c.469+2T>A) at the exon-intron boundary in LRPPRC gene was identified. Sanger validation confirmed the autosomal recessive inheritance of the identified variant. According to ACMG criteria of variant classification PVS1 and PM2 suggest the identified variant in LRPPRC gene to be likely pathogenic. Conclusion: To the best of our knowledge, this variant has not been reported in LRPPRC gene before. Our research not only identifies a novel variant in LRPPRC gene but also confirms the un-resolved molecular diagnosis of the family. WES can be used as first line diagnostic tool in familial cases; especially in those cases if detailed clinical phenotyping is not possible. Once the molecular diagnosis is confirmed in a family, the patients may be re-assessed for their detail clinical phenotypes for establishing a clear genotype-phenotype correlation.